Framing trauma leaders’ request in emergency care interactions: A multimodal analysis using eye-tracking glasses - Tsuchiya, Keiko; Coffey, Frank; Mackenzie, Andrew; Atkins, Sarah; Chalupnik, Malgorzata; Timmons, Stephen; Whitfield, Alison; Vernon, Mike; Crundall, David (Communication and Medicine, 2021)
A team leader’s request is a crucial factor for successful team interaction to ensure patient safety in emergency care. This study examines how team leaders accomplish and frame immediate requests through language use and corresponding eye-movement patterns in emergency care simulation, focusing on when the team is led by a senior doctor (SD) and when it is led by a junior doctor (JD). The team included two foundation doctors, who are in their first two years in medical practice, two emergency department (ED) nurses and one ED expert. They were recorded undertaking separate simulated operations on a simulated patient, and the team leader wore eye-tracking glasses. Interactional linguistic and multimodal analyses of video, audio and eye-movement data revealed that SD made immediate requests to the team members with multimodal emphasis – i.e., gazed at the recipients and addressed them verbally, especially when asking for recipients’ actions – while JD often used only gaze in requesting such actions. Although our study has limitations in terms of the small size of the data, the findings nevertheless highlight that the leader’s requesting was framed and ascribed in the continuum from a question to an instruction through co-construction of joint action with recipients in the social interaction.